A Global Outreach by two Malaysians Success Story Unveiled - Kumaran, Kadirgama; Wan Sharuzi, Wan Harun (2020)
Universiti Malaysia Pahang (UMP) received the Qatar National Research Fund (QNRF) worth RM350,000 from a total of RM3.2 million in 2016 by Associate Professor Ts. Ir. Dr. Kumaran Kadirgama and Associate Professor Ts. Ir. Dr. Wan Sharuzi Wan Harun. The grant is a collaboration with Qatar University, Hamad Medical Corporation, and Rutgers University. The achievement of the project shows that Universiti Malaysia Pahang can compete with other universities in the world.